The effect of sequenced accompaniments on rhythmic accuracy and playing fluency of beginner piano students aged six to eight / Doreen Chai Hui San - Doreen Chai , Hui San (2018)
This research study aims to examine beginning piano students’ rhythmic accuracy and playing fluency in each of the two conditions: with and without the use of sequenced accompaniments during piano teaching through quasi-experimental design. Subjects (N=60) of six to eight years old beginning piano students were randomly assigned to treatment group and control group. Subjects were tested on piano pieces of two different styles: March and Swing, with selected rhythmic components. Subjects in the treatment group were taught to practise six rhythm exercises with sequenced accompaniments, while the other group was taught to practise the same rhythm exercises without sequenced accompaniments. Sequenced accompaniments has shown to be effective in increasing rhythmic accuracy and playing fluency of beginning piano students, with a significant difference statistically between the two groups, p < 0.001 for both Piece A and Piece B. Sequenced accompaniment teaching approach was proven to be a universal approach across all ages (from six to eight years old) whereas the conventional rhythm counting method is only suitable for the later age group. The findings of this research study suggested that sequenced accompaniments are effective in music teaching, which fit the cognitive processes of music learning in young children, rather than merely providing fun experiences. The outcome of this experimental research provides new insight in rhythm training for music educators and contributes to the research gaps identified within music technology education research, as well as piano or digital keyboard manufacturing industries in developing new technologies or products to ensure musical growth.